DOC‐2/DAB2 interactive protein destabilizes c‐Myc to impair the growth and self‐renewal of colon tumor‐repopulating cells. Issue 11 (12th September 2021) - Li, Haiou; Zhou, Yunjiao; Wang, Meng; Wang, Haizhou; Zhang, Yangyang; Peng, Ruyi; Zhang, Ruike; Zhang, Meng; Zhang, Mengna; Qiu, Peishan; Liu, Lan; Zhao, Qiu; et al.
Abstract: Colorectal carcinoma (CRC) remains a huge challenge in clinical treatment due to tumor metastasis and recurrence. Stem cell‐like colon tumor‐repopulating cells (TRCs) are a subpopulation of cancer cells with highly tumorigenic and chemotherapy resistant properties. The core transcription factor c‐Myc is essential for maintaining cancer stem‐like cell phenotypes, yet its roles and regulatory mechanisms remain unclear in colon TRCs. We report that elevated c‐Myc protein supported formation and growth of TRC spheroids. The tumor suppressor DOC‐2/DAB2 interactive protein (DAB2IP) suppressed c‐Myc expression to inhibit TRC expansion and self‐renewal. Particularly, DAB2IP disrupted c‐Myc stability through glycogen synthase kinase 3β/protein phosphatase 2A‐B56α‐mediated phosphorylation and dephosphorylation cascade on c‐Myc protein, leading to its eventual degradation through the ubiquitin‐proteasome pathway. The expression of DAB2IP was negatively correlated with c‐Myc in CRC specimens. Overall, our results improved mechanistic insight into how DAB2IP suppressed TRC growth and self‐renewal. Abstract : We reported that elevated c‐Myc protein supported formation and growth of tumor‐repopulating cell (TRC) spheroids. The tumor suppressor DOC‐2/DAB2 interactive protein (DAB2IP) suppressed c‐Myc expression to inhibit TRC expansion and self‐renewal. Particularly, DAB2IP disrupted c‐Myc stability through glycogen synthase kinase 3β/protein phosphatase 2A‐B56α‐mediated phosphorylation and dephosphorylation cascade on c‐Myc protein, leading to its eventual degradation through the ubiquitin‐proteasome pathway.